Managing emotions in psychosis: Evaluation of a brief DBT‐informed skills group for individuals with psychosis in routine community services. (7th February 2022) - Lawlor, Caroline; Vitoratou, Silia; Duffy, James; Cooper, Ben; De Souza, Tanisha; Le Boutillier, Clair; Carter, Ben; Hepworth, Claire; Jolley, Suzanne
Abstract : Objectives: Individuals with psychosis report that emotion regulation (ER) difficulties are treatment priorities, yet little is known about how targeted ER interventions may help. We evaluated a new eight‐session Dialectical Behavioural Therapy (DBT)–informed skills group specifically adapted for individuals with psychosis: the Managing Emotions Group (MEG) in diverse, inner‐city community services. Method: A mixed‐method design was utilised to assess the feasibility (acceptability and potential clinical impact) of local delivery of MEG. Uptake, completion (≥50% of sessions), post‐session satisfaction ratings, and thematic analysis of qualitative feedback from 12 completers assessed acceptability. Pre–post‐intervention changes in psychological distress, self‐reported ER difficulties, and adaptive ER skill use assessed potential clinical impact. Results: Forty‐eight individuals (81% of attenders) completed the intervention ( M age = 43, 54% female) of whom 39 completed pre‐ and post‐group measures. Participants reported high satisfaction and meaningful improvements in understanding and managing emotions, with positive impact on daily life. Self‐reported psychological distress, ER difficulties, and adaptive ER skill use significantly improved, with medium‐to‐large pre‐post effects ( d = 0.5–0.7) except lack of emotional clarity ( d = 0.3). Conclusions: MEG was feasible and acceptable, and a future feasibility randomised controlled trial is warranted. Practitioner points: Individuals with psychosis report that support with their emotions is a priority. Brief interventions for emotion regulation difficulties are acceptable to individuals with psychosis and can be feasibly delivered in a local outpatient service. Distress and emotion regulation difficulties and skills improved significantly from pre–post treatment for clients completing the managing emotions group. Further implementation and evaluation are needed to support continued refinement to meet the needs and priorities of individuals with psychosis.